Digital Families and the Threat of Online Gambling: Legal Challenges in Protecting Children in Indonesia - Muzacky, Ahmad; Purwanto, Muhammad Roy (GoAcademica Research & Publishing, 2025)
Online gambling has created new forms of rifts in the family structure that occur silently but have a wide impact, especially on children. The fragmentation of relationships in digital households disrupts parenting functions and creates vulnerable psychosocial conditions for children in the domestic environment. Unfortunately, the child protection system in Indonesia lacks a mechanism to respond to indirect threats arising from the dynamics of cyberspace within the family. This study aims to critically examine the limitations of the legal and social systems in protecting children from family disintegration due to online gambling. The study employed a qualitative approach, drawing on library research and the analysis of relevant literature and secondary data. Data were analyzed using a thematic approach to uncover regulatory and social gaps that have not been able to anticipate structural damage in digital families. The results of the study show that existing regulations are still partial, and sectoral, and fail to touch on the complexity of families exposed to destructive digital practices. Child protection has not integrated new risk indicators that arise from uncontrolled online environments. A redesign of the child protection system is needed to be more inclusive, multisectoral, and adaptive to the challenges of digital families so that the best interests of children can be guaranteed comprehensively.